Motivating Factors in Foreign Volunteering: Tibor Péchy’s Enlistment in the Anglo-Boer War - Szabó-Zsoldos, Gábor (Acta Neerlandica, 2023)
Twelve Hungarian volunteers have been identified so far among the 2,500 pro-Boer foreign volunteers who were ready to sacrifice their lives in the war between the Boer republics and the British Empire (1899–1902). The overwhelming majority of these volunteers travelled to South Africa to join the commandos of the Boers following the escalation of the conflict. Tibor Péchy was one of the Hungarian combatants, but in contrast with the other Hungarian volunteers, he had been living in South Africa since 1896. This makes him a special Hungarian participant of the Anglo-Boer War. The present paper analyses the motivating factors behind Péchy’s enlistment with the Boers.